MEMORY, HISTORY, AND PLURIPOTENCY: A REALIST VIEW OF LITERARY STUDIES. - Goffeney, Martin (Cosmos & History, 2013)
Speculative realism has, over the course of its rapid and controversial emergence in the past decade, been frequently criticized from the perspective of historical materialism, for its putative reliance on abstraction and eschewal of a sufficiently rigorous ideological alignment. This paper takes such critiques as a starting point for an examination of the contributions recent thought in the area of speculative realism has to offer the study of the humanities - specifically, the study of literature and literary history. In particular, contemporary realist thought has the potential to enable scholars of literature to move beyond the anthropocentric and specialized notions of history as an exclusively cultural entity, which have dominated the discipline since the twentieth century. Paying especially close attention to the work of Graham Harman and Manuel DeLanda, it is my argument that emergent realist philosophy offers literary scholars a set of powerful conceptual tools which can be put toward the work of accounting for the hitherto neglected ontological status of the literary text - illuminating the status of the text as a particular variety of real and physical object that participates in a system of real and physical history and memory.